Consistency, Cohesion, and Harmony in the Holy Qur’an and the Noble Prophet’s Sunnah - Esmatt, Sohila Ahmad (Journal of Educational Analytics, 2024)
Therefore, this article aims to clarify the harmony, coherence, and consistency in some Quranic verses and Prophetic hadiths that have not been discussed in depth. Sufficient, and therefore it was necessary to pay attention to focus on some verses of the Holy Qur’an and the Prophet’s Hadith to know how there is harmony and consistency between its words, expressions, and positions. This article used the qualitative approach with the literature review method and its steps are as follows: defining the research, then searching for relevant reading sources, reading and understanding them, then taking notes, then summarizing the readings that were found, and finally conducting the literature review and writing general opinions. The article contains five noble verses and two noble hadiths, and from the study and analysis in this article, it was concluded that 1- Ease and redundancy in speech have verbal benefits and clear evidence of harmony. 2- The use of the three types of verbs, whether past, present, or imperative, is of great importance for determining the position. 3- The use of metaphor and simile brings the meaning closer to the mind of the listener and reader and makes the text coherent without disruption. Hence the importance of writing in consistency, cohesion, and harmony in the words of the Messenger of God and the words of the Almighty God.